Successful treatment of advanced stage yolk sac tumour of extragonadal origin: a case report and review of literature - Rudaitis, Vilius; Mickys, Ugnius; Katinaitė, Justina; Dulko, Justyna (Acta medica Lituanica, 2016)
Background. Yolk sac tumour diagnosis should be considered for young age patients admitted to the hospital with non-specific complaints of widespread disease. Correct diagnosis and carefully planned treatment is the key to a successful outcome. Methods and materials. We present a rare case of a widespread yolk sack tumour of a uterine broad ligament. Our team directed a special attention towards the patient’s young age, advanced disease, and fertility sparing strategy of treatment. Results and conclusions. Stage IV yolk sac tumours of extragonadal origin are rarely reported in the literature. Hence, diagnosis and treatment often pose a challenge for emergency care unit doctors, gynaecologists, and oncologists. However, it can be a potentially curable disease. Moreover, patients’ fertility can also be preserved. We believe that further analysis of similar cases is necessary to study outcomes and evaluate patients’ responses to a sequence of medical decisions taken for this specific case.